(untitled) (Cadernos de Sociomuseologia, 2022)
The community project Letras Prá Vida has been developed in Portugal since 2015 and is coordinated by the Escola Superior de Educação of the Polytechnic Institute of Coimbra. Within the scope of its socio-educational intervention dimension, it promotes literacy workshops, the "Letras Prá Vida"; for the promotion of digital literacy, Teclas Prá Vida; and Músicas Prá Vida, which use music as an instrument at the service of humanization, in an inclusive and intergenerational approach. These workshops contribute to the development of different literacies, intergenerational dialogue, equal learning opportunities, empowerment, social inclusion, combating loneliness and isolation, active aging, civic participation, democratic citizenship and education. to health. Added to this intervention dimension, based on in-service learning, a participatory and critical research-action dimension, a formative dimension of adult education and literacy and a community of practice that contributes, through the critical friends of the project, among which we include Paulo Freire. In a liberating, democratic, and openly political practice, we defend education as a public good for all, valuing non-formal adult education and the education of older adults as a right and an investment. This unfinished reflection on how Paulo Freire lives at the heart of Letras Prá Vida that we present here is an invitation to the action of hope. Keywords: Literacy with the Heart; Adult Education; Letters for Life; Paulo Freire; Pedagogy of Hope